The Influence of Teacher's Teaching Style on Students' Learning Motivation and Creativity in Grade X and XI in High School - Karundeng, Ferry F.; Rawis, Joulanda A. M.; Tuerah, Roos M. S. (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The Purpose of This Study was to determine the Effect of Teacher Teaching Style on Motivation and Learning Creativity of Students in Classes X and XI in SMA Negeri 2 Tondano, Minahaa Regency. The method used in this study is multiple linear regression. With the results of research as follows: 1. Based on the results of the analyst of variance testing that the value of Sig = 0.00. Because the value of Sig < 0.05 the H0 is accepted, as well as if you look at the Ftest. With Fcount = 520,654 > Ftable = 1,680. So it can be concluded that there is an influence of Teacher's Teaching Style On The Learning Motivation of Students of Class X and XI in SMA Negeri 2 Tondano, Minahasa Regency. Based on the result of the analyst of variance testing that the value of Sig = 0.00. Because the value of Sig < 0.05 the H0 is accepted, as well as if you look at the Ftest. With Fcount =311,583> Ftable = 1.680. So it can be concluded that there is an influence of Teacher's Teaching Style on the Learning Creativity of Students of Class X and XI in SMA Negeri 2 Tondano, Minahasa Regency. Based on the result of the analyst of variance testing that the value of Sig = 0.00. Because the value of Sig < 0.05 the H0 is accepted, as well as if you look at the Ftest. With Fcount =290,567> Ftable = 1.680. So it can be concluded that there is an influence of Teacher's Teaching Style On the Learning Motivation and Creativity of Students of Class X and XI in SMA Negeri 2 Tondano, Minahasa Regency. The study of conclusions that is a significant determine the Effect of Teacher Teaching Style on Motivation and Learning Creativity of Students Class X and XI in SMA Negeri 2 Tondano, Minahaa Regency. Based on the conclusion above it is recommended as follows: 1. The teacher always motivates students the creativity power. 2 The teachers must develop the potential of students including fostering students. 3. the teacher always provides support and assistance to understand that learning is very important the development of knowledge.